Mutational analysis of the GAP-related domain of the neurofibromatosis type 1 gene in Brazilian NF1 patients - Trovó, Alessandra B. [UNESP]; Goloni-Bertollo, Eny M.; Mancini, Ulises M. [UNESP]; Rahal, Paula [UNESP]; Azevedo Jr., Walter F. de [UNESP]; Tajara, Eloiza H. [UNESP] (Sociedade Brasileira de Genética, 2004)
Neurofibromatosis type 1 (NF1) is a common autosomal dominant disorder caused by mutations in the NF1 gene. In the present study, a total of 55 unrelated NF1 patients were screened for mutations in the GAP-related domain/GRD (exons 20-27a) by single-strand conformation polymorphism (SSCP). Four different mutations were identified and, taken together, they comprise one nonsense substitution (Q1189X), one deletion (3525-3526delAA), one missense substitution (E1356G) and one mutation in the splice acceptor site (c.4111-1G>A). One novel polymorphism (c.4514+11C>G) and other three putative polymorphisms were also found (c.3315-27G>A, V1146I and V1317A). Genotype-phenotype correlations were investigated, but no particular association was detected.
Keywords: gene NF1; GRD; Neurofibromatosis type 1; Mutations; Polymorphism